Weak versus strong sustainability : exploring the limits of two opposing paradigms - Neumayer, Eric (Cheltenham Edward Elgar Publishing Ltd., 2010)
Summary: This insightful book explores the limits of the two opposing paradigms of sustainability in an accessible way. It examines the availability of natural resources for the production of consumption goods and services, and the environmental consequences of economic growth. The critical forms of natural capital in need of preservation given risk, uncertainty and ignorance about the future are also examined. The author provides a critical discussion of measures of sustainability. As indicators of weak sustainability, he analyses Genuine Savings and the Index of Sustainable Economic Welfare, also known as the Genuine Progress Indicator. Indicators of strong sustainability covered include ecological footprints, material flows, sustainability gaps and other measures, which combine the setting of environmental standards with monetary valuation.
1. Introduction and overview --
2. Sustainable development --
3. Resources, the environment and economic growth: is natural capital substitutable? --
4. Preserving natural capital in a warld of risk, uncertainty and ignorance --
5. Measuring weak sustainabilty --
6. Measuring strong sustainability --
7. Conclusions --
Summary from Elgaronline
Bibliography: p. 210-259
Includes index
Keywords: Economic development; ECONOMIC DEVELOPMENT; SUSTAINABLE DEVELOPMENT; ENVIRONMENTAL EFFECTS; ENVIRONMENTAL ECONOMICS; NEOCLASSICISM